Triptolide-induced hepatotoxicity is mediated by NLRP3-dependent pyroptosis and inhibited by mitophagy - Yuerui Su; Pengcheng Li; Kun Zhou; Yinxia Chang; Zhihua Luan; Bo Han; Huifang Li; Jinhong Ren; Haixue Zhang; Yanming Wei (Food and Chemical Toxicology, 2026)

Long-term legume-legume shrub assembly enhances sandy soil multifunctionality via reinforced plant-soil-microbe feedbacks - Wangsuo Liu; Kaiyang Qiu; Yingzhong Xie; Yanming Zhang; Gangtie Li; Xinning Han; Wenfei Dong (Applied Soil Ecology, 2026)

Interspecific Competition Between Dominant Macrobenthic Species and Meretrix meretrix in a Clam Aquaculture Area - Haopeng Hu; Yan Liu; Longyu Liu; Peng Gao; Yanming Sui; Shuai Han; Mei Jiang; Lei Li (Fishes, 2026)
Understanding niche differentiation and interspecific coexistence patterns of macrobenthos provides critical references for ecological assessment of bivalve aquaculture. Seasonal field surveys (Autumn 2023–Summer 2024) across 12 sampling sites were conducted in an intensive Meretrix meretrix tidal flat farm in Rudong, Jiangsu. Synchronous water depth, sediment grain size and total organic carbon (TOC), and salinity were measured at each station to characterize habitat gradients; no unfarmed reference tidal flats were included, so all community patterns only reflect within-farm variation. The study area has sustained 10-year continuous bottom culture with baseline juvenile stocking density of 250 ind./m2 and twice-yearly manual harvesting. A total of 58 macrobenthic taxa were identified, and 13 dominant species were screened with a dominance index threshold Y > 0.02. All abundance data were fourth-root-transformed before Bray–Curtis community analysis to reduce bias of hyper-abundant taxa. Standardized Shannon niche breadth (0–1 normalized, r = 48 site–season composite units) and permutation-tested (999 replicates) Pianka niche overlap/similarity coefficients were calculated to quantify resource utilization similarity. Niche breadth ranged from 0.018 to 0.971, with farmed M. meretrix showing the maximum value, indicating broader seasonal resource adaptation. High niche overlap (>0.50) was detected between M. meretrix and four wild dominant species (Nephtys californiensis, Moerella iridescens, Lingula anatina, Umbonium thomasi). Notably, niche metrics derived solely from spatial abundance data cannot directly confirm interspecific competition or trophic segregation; the stable coexistence observed in our assemblage is tentatively hypothesized to be driven by vertical sediment partitioning and divergent feeding guilds based on published functional studies, without direct in situ trophic or stratified sediment evidence from this work. Hierarchical UPGMA clustering (0.35 Bray–Curtis distance threshold) and corrected NMDS ordination (48 site–season units, dominant-species fitted vectors) illustrated distinct functional groups. Based on the observed niche convergence among filter-feeding bivalves under local farming conditions, the range of 230–280 ind./m2 is presented as an observational reference. Controlled manipulative experiments with gradient stocking densities are needed to test whether this range can balance aquaculture yield and benthic biodiversity.

Genome-wide AP2/ERF analysis identifies HmaERF87 as a positive regulator of Hydrangea macrophylla leaf spot resistance - Shuyuan Chen; Xintong Liu; Chengwei Zhang; Ziqin Zhang; Huijie Chen; Yong Han; Shuangshuang Chen; Jing Feng; Guangling Wang; Chang Li; Zedong Wu; Yanming Deng (Plant Cell Reports, 2026)

Interactive Toxic Impacts of Thermal Stress and Residual Chlorine on Growth, Nutritional Composition and Digestive Physiology in Meretrix meretrix - Shuai Han; Sitong Wang; Haopeng Hu; Wenping Yang; Shuo Qin; Peng Gao; Yanming Sui; Yebing Yu; Mei Jiang; Lei Li (Fishes, 2026)
Thermal elevation and residual chlorine pollution are two anthropogenic stressors that co-occur in estuarine waters affected by coastal power plant effluents. A 30-day exposure experiment was established with six treatment combinations comprising three temperatures (27 °C, 28 °C, and 30 °C) and two residual chlorine concentrations (0 mg/L and 0.02 mg/L) on Meretrix meretrix. Sampling was conducted on days 0, 10, 20 and 30 of the trial. The results indicated that elevated temperature (30 °C) significantly suppressed shell height and total body weight, while residual chlorine (0.02 mg/L) exerted time-dependent effects on shell length and width, with a significant interactive effect on shell length only at day 30. Crude lipid content declined with increasing temperature and residual chlorine exposure, whereas moisture and ash contents showed significant two-way interactions at all sampling time points. Intestinal amylase activity was continuously regulated by both stressors, with interactive responses on days 10 and 20, and was significantly suppressed under combined high temperature and residual chlorine stress. Collectively, we infer that combined exposure to elevated temperature and residual chlorine impairs shell growth, muscle biochemical composition and intestinal amylase activity of M. meretrix. Long-term experiments are required to further clarify the joint toxic effects of thermal stress and residual chlorine on the clam species.

Retraction notice to “Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices” [Sci. Total Environ. 925 (2024) 171564] - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2026)

RTK traverse: a multi-user RTK model based on kinematic reference stations - Siyao Wang; Peiyuan Wang; Junqiang Han; Fang Cheng; Shuaihe Gao; Yanming Guo; Xiaochun Lu (Advances in Space Research, 2026)

Distinct cytotoxicity of water disinfection byproducts in human uroepithelium and Chinese hamster ovary cells - Jiaojiao Xie; Jian Han; Yanming Liu; Birget Moe; Qiming Shen; Tongtong Xiang; Chun-Gang Yuan; Xing-Fang Li (Journal of Environmental Sciences, 2026)

Spinel MnFe2O4-anchored biochar for robust peroxymonosulfate activation: Efficient Bisphenol A degradation with mechanistic insights and practical application - Fanyue Meng; Bin Fang; Yijin Han; Bing Song; Yanming Wang; Yuexing Wei (Journal of Water Process Engineering, 2026)

Unraveling urban surface heat dynamics through deep ensemble machine learning - Guansheng Han; Jiqing Zhang; Yuan Gao; Min Zhang; Min Chen; Yanming Liu (Building and Environment, 2025)

TFAP2A-regulated CRNDE enhances colon cancer progression and chemoresistance via RIPK3 interaction - Xin Gao; Yanming Huang; Tonghui Wei; Jingmin Xue; Filippov Iurii; Laishou Yang; Liying Wang; Hao Li; Genshen Mo; Yuze Huang; Haonan Xie; Hang Wang; et al. (Functional & Integrative Genomics, 2025)

Activation of Rab7-mediated lipophagy is required for triptolide to induce ferroptosis in hepatic cells - Shan Liu; Yuerui Su; Bo Han; Liang Yin; Huifang Li; Yingli Wang; Kun Zhou; Pengcheng Li; Yanming Wei (Food and Chemical Toxicology, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Quantifying and modeling of coal permeability spatiotemporal response: Implications for gas recovery and CO2 sequestration - Jinming Zhang; Xiaowei Hou; Shimin Liu; Yanming Zhu; Ang Liu; Long Fan; Yingjin Wang; Han Zhang (Fuel, 2025)

Groundwater storage anomalies projection by optimized deep learning refines groundwater management in typical arid basins - Xiaoya Deng; Guangyan Wang; Feifei Han; Yanming Gong; Xingming Hao; Guangpeng Zhang; Pei Zhang; Qianjuan Shan (Journal of Hydrology, 2025)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

The disruptive effect on the bacterial cell wall explored of the ultrasmall particle-sized Ag nanoparticles supported with Zn Cu-based hybrid nanoagents - Shaobo Guo; Xu Liu; Huihui Chen; Yanming Qiao; Zhifeng Liu; Dan Zhang; Guo Ting; Xiaohui Ji; Hao Han; Tanlei Zhang (Journal of Environmental Chemical Engineering, 2024)

Synergistic Effects of Hydroxychloride and Organic Zinc on Performance, Carcass Characteristics, Liver and Tibia Mineral Profiles of Broiler Chickens - Vahideh Sadr; Hoai Thi Thanh Nguyen; Lane Pineda; Yanming Han; Mehdi Toghyani (Biological Trace Element Research, 2024)
This study investigated the potential synergism between hydroxychloride and organic zinc (Zn) at different levels on performance and carcass characteristics of broiler chickens. There were seven experimental diets including a negative control diet without any supplemental Zn, and six diets with 80 mg/kg added Zn in the forms of ZnSO 4 , hydroxychloride Zn (HCZ) and organic Zn (ORZ), and a combination of HCZ and ORZ at 40 mg/kg HCZ + 40 mg/kg ORZ (HCZ40-ORZ40), 55 mg/kg HCZ + 25 mg/kg ORZ (HCZ55-ORZ25), and 70 mg/kg HCZ + 10 mg/kg ORZ (HCZ70-ORZ10). Each diet was replicated eight times with 17 chicks per replicate. On day 35, HCZ70-ORZ10 and HCZ40-ORZ40 diets resulted in the highest body weights ( P < 0.05). Throughout the entire production period (1–35 days), all HCZ and ORZ diets significantly improved feed conversion ratio (FCR) compared to PC ( P < 0.05), with HCZ40-ORZ40 showing the lowest FCR. Breast meat yield was lower in NC-fed birds, while HCZ80 and HCZ70-ORZ10 groups had the lowest abdominal fat weight ( P < 0.05). Liver and gizzard weight, tibia breaking strength, and ash percentage, footpad dermatitis, and hock burns were not affected. Tibia Zn content was higher in HCZ or ORZ-supplemented birds compared to NC ( P < 0.05), whereas other minerals in tibia and liver were unaffected. In summary, the absence of supplemental Zn negatively affects growth and carcass characteristics, whereas replacing ZnSO 4 with HCZ, ORZ, or their combinations improves bodyweight and FCR. HCZ70-ORZ10 and HCZ40-ORZ40 were identified as optimal combinations for maximizing feed efficiency.

Antibacterial effect of the metal nanocomposite on Escherichia coli - Shaobo Guo; Xu Liu; Huihui Chen; Jiawei Wang; Yanming Qiao; Tanlei Zhang; Xiaohui Ji; Hao Han; Zhifeng Liu; Ying Bai; Jin Tang (Journal of Hazardous Materials, 2024)

RETRACTED: Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2024)

The Neurovascular Unit Dysfunction in the Molecular Mechanisms of Epileptogenesis and Targeted Therapy - Xiuxiu Liu; Ying Zhang; Yanming Zhao; Qian Zhang; Feng Han (Neuroscience Bulletin, 2024)
Epilepsy is a multifaceted neurological syndrome characterized by recurrent, spontaneous, and synchronous seizures. The pathogenesis of epilepsy, known as epileptogenesis, involves intricate changes in neurons, neuroglia, and endothelium, leading to structural and functional disorders within neurovascular units and culminating in the development of spontaneous epilepsy. Although current research on epilepsy treatments primarily centers around anti-seizure drugs, it is imperative to seek effective interventions capable of disrupting epileptogenesis. To this end, a comprehensive exploration of the changes and the molecular mechanisms underlying epileptogenesis holds the promise of identifying vital biomarkers for accurate diagnosis and potential therapeutic targets. Emphasizing early diagnosis and timely intervention is paramount, as it stands to significantly improve patient prognosis and alleviate the socioeconomic burden. In this review, we highlight the changes and molecular mechanisms of the neurovascular unit in epileptogenesis and provide a theoretical basis for identifying biomarkers and drug targets.

Camellia meal-based adhesive with synergistic crosslinking of physical and chemical interaction for preparing aldehyde-free, anti-mildew, water-resistant wood-based composites - Hanzhang Wang; Siqi Zhao; Wei Zhang; Shifeng Zhang; Yanming Han (Journal of Cleaner Production, 2024)

Tetrabromobisphenol a and its alternative tetrachlorobisphenol a induce oxidative stress, lipometabolism disturbance, and autophagy in the liver of male Pelophylax nigromaculatus - Yu Han; Hongmei Yang; Zhiqun Liu; Chao Hu; Imane Lamine; Zhiquan Liu; Panpan Gao; Yanming Sui; Pei Zheng; Hangjun Zhang; Xiuying Jia (Science of The Total Environment, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Weakened economic impacts with future intensifying drought in Chinese mainland - Feifei Han; Hongbo Ling; Xiaoya Deng; Junjie Yan; Yanming Gong; Guangpeng Zhang; Yuanzhi Ma (Journal of Cleaner Production, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Ocean ambient noise on the Chukchi Plateau and its environmental correlates - Xuejing Mo; Hongtao Wen; Yanming Yang; Hongtao Zhou; Jingwei Yin; Xiao Han; Hongxia Chen; Hailin Ruan (Marine Environmental Research, 2023)

Photothermal and Concus Finn capillary assisted superhydrophobic fibrous network enabling instant viscous oil transport for crude oil cleanup - Ting Dong; Yanhui Liu; Na Tian; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Under-ice ambient noise in the Arctic Ocean: observations at the long-term ice station - Xiao Han; Jingwei Yin; Yanming Yang; Hongtao Wen; Longxiang Guo (Acta Oceanologica Sinica, 2020)

LncRNA HCG18 is critical for vascular smooth muscle cell proliferation and phenotypic switching - Yanjiao Lu; Jingjing Guo; Shengnan Zhu; Han Zhang; Qing Zhu; Yanming Li (Human Cell, 2020)

Tsmu solution improves rabbit osteochondral allograft preservation and transplantation outcome - Famin Cao; Jianhong Qi; Hongqiang Song; Di Xie; Lu Zhou; Yunning Han; Hao Li; Qi Wu; Jun Dong; Yanming Zhang (Cell and Tissue Banking, 2018)